دور المسؤولية الاجتماعية في تعزيز سمعة المنظمة: (دراسة حالة شركة شيكان للتأمين وإعادة التأمين المحدودة للعام 2017م) - د. محمد يوسف الشيخ نور الهادي (White Nile Journal for Studies and Research, 2019)
Abstract The study dealt with the role of social responsibility in enhancing the reputation of the organization. The study of the case of Shikan Insurance and Reinsurance Company in the White Nile State in 2017. The problem of Study was: What is the role of social Responsibility in enhancing the reputation of the Organization? Based on the problem of the Study and hypotheses Developed, the following methods were used: descriptive approach to describe the phenomenon and its variants, and the historical Methodology for tracking previous studies related to the literature of research as well as the case Study methodology and the use of primary and secondary sources and the use of the SPSS. A comprehensive sample was selected for all 42 employees. The study reached a number of results: Social responsibility plays a major role in enhancing the company's reputation. The company is keen to communicate with the community. To consolidate the social mental image to customers. It recommended a number of recommendations, including: to include social responsibility in the message and vision of the company clearly, the need to target certain segments of society permanently.